Identifying dominant river contributions to urban flooding: a scenario-based study of Makassar City - Wulandari, Siska; Pratama, Firman; Andika, Neil; Wongso, Piter; Wijayasari, Winda; Rohmat, Faizal Immaddudin Wira (Frontiers in Built Environment, 2025)
Makassar City, a fast-growing urban center in Eastern Indonesia, is highly vulnerable to flooding due to a combination of extreme rainfall, urban expansion, sedimentation, and a limited flood management system. This study investigates the main contributors to flooding in Makassar, based on the city’s extreme flood event in January 2019 and evaluates the effectiveness of the Bili-Bili Reservoir in mitigating flood impacts through integrated hydrologic–hydrodynamic modeling. A combination of HEC-HMS and HEC-RAS 2D was used to simulate the rainfall runoff processes and model flood inundation. GSMaP satellite rainfall data, land cover, soil type, and topographic information (FABDEM + river cross-section) were integrated into the model. Additional terrain data from OSM-B highlights urban areas characterized by dense building development. The validation process was conducted by comparing the modeling output against the inundation maps provided by the local government. Scenario simulations with 20-year return period (Q20) discharges from the Tallo River, Jenelata River, and Bili-Bili Reservoir outflow were used to assess their individual and combined impacts on flooding. Findings indicate that the Tallo River is the dominant contributor to flooding, while reservoir releases and Jenelata River inflow triggered additional inundation in downstream areas. The Bili-Bili Reservoir reduced upstream flooding but was less effective under high-inflow conditions. Discrepancies between model results and reported flood extents in several districts suggest other contributing mechanisms, including urban drainage inadequacies. This study’s findings emphasize the need for more targeted flood mitigation strategies, underscoring the importance of optimizing reservoir operations, managing sedimentation, and exploring storage interventions within Makassar City’s river system to strengthen urban flood resilience.